1998
DOI: 10.1093/bja/80.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Combining propofol with morphine in patient-controlled analgesia to prevent postoperative nausea and vomiting

Abstract: We have studied the antiemetic effects of propofol when mixed with morphine in a patient-controlled analgesia (PCA) pump after major gynaecological surgery. In a double-blind, randomized, controlled study, 50 women, ASA I or II, received a standardized anaesthetic comprising thiopental, morphine, atracurium, nitrous oxide and oxygen with enflurane, and received postoperative PCA with morphine mixed with either 1% propofol or lvelip. The PCA bolus was morphine 1 mg with propofol 5 mg or lvelip 0.5 ml, with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Bree et al studied the antiemetic effects of propofol when mixed with morphine in a patient‐controlled analgesia (PCA) pump after major gynecological surgery. Propofol when mixed with morphine did not decrease the incidence of nausea and vomiting (20). In a study by Grattidge subhypnotic infusion of propofol had no antiemetic effect in patients receiving intrathecal morphine for pain relief after major arthroplasty (21).…”
Section: Discussionmentioning
confidence: 99%
“…Bree et al studied the antiemetic effects of propofol when mixed with morphine in a patient‐controlled analgesia (PCA) pump after major gynecological surgery. Propofol when mixed with morphine did not decrease the incidence of nausea and vomiting (20). In a study by Grattidge subhypnotic infusion of propofol had no antiemetic effect in patients receiving intrathecal morphine for pain relief after major arthroplasty (21).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation by Jadad's scoring system, operation (setting), number of subjects, dosing regimen of morphine, dosing regimen of the test drug, number of patients who developed nausea and/or vomiting, and eŠec-tiveness are shown in this table. The test drug was droperidol in 11 studies, 7,8,12,[16][17][18][19][20][21] metoclopramide in 5 studies, 9,10,16,21) dexamethasone in 6 studies, [22][23][24] propofol in 4 studies, [25][26][27][28] and ondansetron in 5 studies. 9,12,15,22) The results of testing the lack of homogeneity the results of studies for each of the four test drugs are shown.…”
Section: From the Medline Database And Cochranmentioning
confidence: 99%
“…In populations that include a wide range of operative procedures, the incidence ranges from 22% to 52% (1,2). The incidence seems to increase in patients receiving patientcontrolled analgesia (PCA), where rates of 68%-100% for PON and POV have been recorded (3,4).…”
mentioning
confidence: 99%